A review of the animal influenza viruses and their impact on human health - Shreya Veggalam; Sriguna Bannur; Venkataramana Kandi (Discover Public Health)
Abstract Influenza viruses are a complex group of microorganisms that cause flu-like illnesses in humans and animals. These viruses can multiply and infect different animal hosts like the pigs, and birds. Furthermore, influenza type A viruses have the potential to undergo significant genetic variations within the hosts and develop into to a novel viral strain with high pathogenic potential. This type of viral evolution can pose health risks to animals and humans. Therefore, it is important to understand the animal influenza viruses and assess their potential to infect humans. This narrative review discusses influenza viruses of animal origin, their epidemiology, transmission dynamics, impact on human health and treatment and preventive strategies including the WHOs one-health intervention, vaccination, and the potential for these viruses to transmit between humans and possibly resulting in pandemics.